2016
DOI: 10.1159/000442936
|View full text |Cite
|
Sign up to set email alerts
|

Routine Use of Probiotics in Preterm Infants: Longitudinal Impact on the Microbiome and Metabolome

Abstract: Background: Probiotics are live microbial supplements that colonize the gut and potentially exert health benefit to the host. Objectives: We aimed to determine the impact of a probiotic (Infloran®: Lactobacillus acidophilus-NCIMB701748 and Bifidobacterium bifidum-ATCC15696) on the bacterial and metabolic function of the preterm gut while in the neonatal intensive care unit (NICU) and following discharge. Methods: Stool samples (n = 88) were collected before, during, and after probiotic intake from 7 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 25 publications
8
80
2
Order By: Relevance
“…It is well accepted that the metabolite profile of the gut lumen is dependent on the structure and function of the resident microbiota (50,51). One recent study evaluated the use of probiotics in preterm infants and their impact on the microbiome and metabolome and concluded that metabolite profiles are different between probiotic and control groups, which strengthens our results on the discrimination of B and F infants over time (52). Although little insight is available for nontargeted metabolomics of healthy B and F infants, Wang et al (53) identified 15-methylhexadecanoic acid, galactitol, and maltose as discriminating metabolites for breastfeeding, and b-alanine, dodecanoic acid, glycolic acid, decanoic acid, and tyramine for formula feeding.…”
Section: Discussionsupporting
confidence: 83%
“…It is well accepted that the metabolite profile of the gut lumen is dependent on the structure and function of the resident microbiota (50,51). One recent study evaluated the use of probiotics in preterm infants and their impact on the microbiome and metabolome and concluded that metabolite profiles are different between probiotic and control groups, which strengthens our results on the discrimination of B and F infants over time (52). Although little insight is available for nontargeted metabolomics of healthy B and F infants, Wang et al (53) identified 15-methylhexadecanoic acid, galactitol, and maltose as discriminating metabolites for breastfeeding, and b-alanine, dodecanoic acid, glycolic acid, decanoic acid, and tyramine for formula feeding.…”
Section: Discussionsupporting
confidence: 83%
“…Our study contributes to a recent finding on the effects of Infloran in the infant gut, whereby increased levels of bifidobacteria were found during and after probiotic administration, and a reduction in the abundance of Lactobacillus  reported after discharge 17. However, the sample size in our study, 8–10 infants per group, is a major limitation as there are many confounding factors that can affect the growth of bifidobacteria during this initial developmental period in life.…”
Section: Discussionmentioning
confidence: 70%
“…have generally shown reduced incidences of NEC [27, 28] and bifidobacteria are known to play fundamental roles in the development and maintenance of a healthy gut microbiome [29, 30]. Thus, the high abundance of bifidobacteria may contribute to the improved health status by aiding gut maturation and preventing over-expression of potentially damaging pathways, although it is also possible that a higher abundance of bifidobacteria simply acts as a marker for a more healthy gut, rather than being directly causative in preterm infants.…”
Section: Discussionmentioning
confidence: 99%